Efeito da contrapressão e do resfriamento da turbina no desempenho de um motor diesel ottolizado para gás natural - Barros, Bruno Vinícius de menezes' (2015)
The cost of the kWh at the peak hour in Brazil may be up to nine times higher than the one at normal hours. This fact has served as motivation for industries, shopping malls, hotels, and so on, to utilize electrical generators. These generator sets generally comprise Diesel engines. The problem is that the exhaust gases from these engines are very harmful to health. On the other hand, Natural Gas, thanks to its high calorific power and its low emissions, is considered a clean-burning alternative fuel. Therefore, the Diesel engines converted to Otto cycle may considerably reduce the environmental pollution. Such a conversion, however, may have in turbocharged engines backpressure effects that increase the temperature of the turbine, reducing the energy efficiency of the engine. The present study analyzes the result and consequences of the replacement of the original manifold by another with smoother curves, as well as the cooling effect on the engine performance of the turbine of a Perkins turbocharged model 1104C-44TAG2, converted to the Otto cycle. First, tests were made running the engine with its original manifold without any cooling, and then, having the turbine cooled with room air. After the replacement of the manifold, new teste were performed. Initially, without cooling the turbine or the manifold. Then, after the replacement of the manifold, other tests ventilating the turbine and the manifold were made. In each test, one has registered: the maximum operation power; temperature of the exhaust gases and the engine consumption in terms of the backpressure due to the manifold. All the tests were performed with the aid of a hydraulic dynamometer. It was noted that the use of the new manifold allowed the reduction on the backpressure. Concerning the maximum power registration there was no difference in terms of the original or the new manifold, because what had limited the power was the temperature on the turbine, which was set at 660 oC. Therefore, whenever the temperature reached this limit, the engine was deliberated stopped. This fact also explains why the ventilation has allowed higher engine powers. The new manifold resulted in fuel reductions.